AL-ISLAM DAN KEMUHAMMADIYAHAN DALAM BERBAGAI ASPEK (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the role of Al-Islam and Kemuhammadiyahan in shaping the character of a progressive and virtuous Muslim community. Al-Islam, as an Islamic teaching derived from the Al-Qur’an and Sunnah, provides universal guidelines for human life. Meanwhile, Kemuhammadiyahan, as a reformist movement in Islam, is based on the principles of tauhid, amar ma'ruf nahi munkar, and tajdid. This research explores various key aspects of Al-Islam and Kemuhammadiyahan, such as aqidah, ibadah, akhlak, social, education, economy, and politics, and how Muhammadiyah implements Islamic teachings in daily life to shape a faithful, knowledgeable, and virtuous Muslim community. This study employs a qualitative approach using literature review as the research method to analyze relevant literature. The findings of this research indicate that Al-Islam and Kemuhammadiyahan contribute significantly to building a just, empowered, and prosperous society.